A PSYCHOANALYTIC READING OF BORN ON A TUESDAY BY ELNATHAN JOHN - MUHAMMAD, HASSAN MUSA (Fırat Üniveristesi, 2022)
Bu çalışmanın amacı, Elnathan John'un Bir Salı Günü Doğdu (2015) adlı romanına psikoanalitik bir okuma sunmaktır. Nijerya'nın en ölümcül terörist grubu olan Boko Haram'ın amansız gaddarlığı, küresel toplumun dikkatini Batı Afrika alt kıtasındaki İslami aşırıcılığın yükselişine çekmiş ve sosyal bilimlerdeki bilim adamlarını İslami köktenciliğe ve özelliklerine kulak vermeye zorlamıştır. Bir Salı Günü Doğdu, İslami köktenciliğin bu özel versiyonunda yer alan sayısız dini, siyasi, ekonomik, sosyal ve psikolojik gücün karmaşık bir ağını tasvir ettiği için Boko Haram terörizminin mükemmellik fenomeninin edebi bir yorumudur. Bu çalışmada, Bir Salı Günü Doğdu'yu eleştirel bir şekilde incelemek ve hem özgün hem de aydınlatıcı bir bulgu ortaya çıkarmak adına edebiyat araştırmalarında psikanalizin kuram ve ilkelerinden yararlanan bir okuma yöntemi olan psikanalitik eleştiri kullanılmıştır. Oedipus kompleksi ve savunma mekanizmaları teorisi gibi Freudyen psikanalitik kavramların ışığında bu çalışma, Bir Salı Günü Doğdu'daki karakterlerin davranışlarını inceleyerek şu soruya yanıt aramaktadır: Nijerya bağlamında İslami aşırıcılığın başlıca nedenleri nelerdir? Bu çalışma, etki etmekte olan diğer faktörlerin varlığını inkar etmese de çalışmanın bulguları İslami aşırılığın ana kaynağının insan psikolojisi (hükümetleri dahil) olduğunu belirlemektedir. Son olarak bu çalışma, psikanalitik eleştirinin hem edebi metinlerin hem de yeterince anlaşılmayan toplumsal terör olgusunun başka bir şekilde erişilemeyecek köklerini ve anlamlarını ortaya çıkarmadaki büyük önemini bir kez daha göstermektedir.

This study aims to offer a psychoanalytic reading of Elnathan John's novel Born a Tuesday (2015). The relentless ferocity of Boko Haram, the Nigerian most deadly terrorist group, has drawn the attention of the global community to the rise of Islamic extremism in the West African sub-continent and compelled scholars in the social sciences to pay attention to the nature of Islamic fundamentalism in the African continent and its peculiarities. Born on a Tuesday is a literary interpretation of the phenomena of Boko Haram terrorism per excellence as the novel depicts a complex web of the numerous religious, political, economic, social and psychological forces involved in this particular version of Islamic fundamentalism. Psychoanalytic criticism, an insightful method of reading which utilises the theories and principles of psychoanalysis in studying literature, has been used in this study in order to analyse Born on a Tuesday critically and come up with a finding that is both original and revealing. By examining the behaviours of the characters in Born on a Tuesday under the light of the Freudian psychoanalytic concepts such as the Oedipus complex and the theory of defense mechanisms, this study attempts at answering the question: what are the major causes of Islamic extremism in Nigerian context? Even though this study does not negate the existence of other contributing factors, its findings establish the psychology of the people (the governments inclusive) as the principal source of the Islamic extremism. Finally, the study also re-affirms the paramount importance of psychoanalytic criticism in revealing the otherwise inaccessible roots and meanings of both literary texts and the poorly understood social phenomenon of terrorism.
Elnathan John'un Bir Salı Günü Doğdu adlı romanına psikanalitik bir okuma
Keywords: Batı Dilleri ve Edebiyatı